Binge‐eating disorder and the outcome of bariatric surgery in a prospective, observational study: Two‐year results. Issue 11 (12th September 2016) - Chao, Ariana M.; Wadden, Thomas A.; Faulconbridge, Lucy F.; Sarwer, David B.; Webb, Victoria L.; Shaw, Jena A.; Thomas, J. Graham; Hopkins, Christina M.; Bakizada, Zayna M.; Alamuddin, Naji; Williams, Noel N.
Abstract : Objective: A previous study reported that preoperative binge‐eating disorder (BED) did not attenuate weight loss at 12 months after bariatric surgery. This report extends the authors' prior study by examining weight loss at 24 months. Methods: A modified intention‐to‐treat population was used to compare 24‐month changes in weight among 59 participants treated with bariatric surgery, determined preoperatively to be free of a current eating disorder, with changes in 33 surgically treated participants with BED. Changes were also compared with 49 individuals with obesity and BED who sought lifestyle modification for weight loss. Analyses included all available data points and were adjusted for covariates. Results: At month 24, surgically treated patients with BED preoperatively lost 18.6% of initial weight, compared with 23.9% for those without BED ( P = 0.049). (Mean losses at month 12 had been 21.5% and 24.2%, respectively; P = 0.23.) Participants with BED who received lifestyle modification lost 5.6% at 24 months, significantly less than both groups of surgically treated patients ( P < 0.001). Conclusions: These results suggest that preoperative BED attenuates long‐term weight loss after bariatric surgery. We recommend that patients with this condition, as well as other eating disturbances, receive adjunctive behavioral support, the timing of which remains to be determined.